2013
DOI: 10.1093/plankt/fbt026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microalgal exudates and intact cells on subtropical marine zooplankton

Abstract: Harmful algal blooms (HABs) affect coastal waters worldwide and very often lead to the disruption of seafood harvesting and commercial activities, because of potential hazards to human health associated with the consumption of contaminated mussels, crustaceans and fish. HAB events are frequently caused by outbreaks of toxin-producing dinoflagellates, which are subject to top-down control by zooplankton. The aim of this study was to analyze the effects of dinoflagellate exudates and intact cells on the survivor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
1
9
1
Order By: Relevance
“…Although Paracalanus sp. nauplii may exhibit adverse effects from feeding upon Alexandrium tamiyavanichii (Silva et al, 2013), we did not detect negative effects on nauplii abundances when relating them to the harmful algae abundance, but a delay in the reaction time likewise in aloricate ciliates, dinoflagellates and calanoid copepods. Accordingly, we based our conclusions for copepods on temporal trends and pCO 2 treatments rather than on possible effects of inedible/harmful food items.…”
Section: Pco 2 Effects On Zooplankton Bloom Timingcontrasting
confidence: 60%
“…Although Paracalanus sp. nauplii may exhibit adverse effects from feeding upon Alexandrium tamiyavanichii (Silva et al, 2013), we did not detect negative effects on nauplii abundances when relating them to the harmful algae abundance, but a delay in the reaction time likewise in aloricate ciliates, dinoflagellates and calanoid copepods. Accordingly, we based our conclusions for copepods on temporal trends and pCO 2 treatments rather than on possible effects of inedible/harmful food items.…”
Section: Pco 2 Effects On Zooplankton Bloom Timingcontrasting
confidence: 60%
“…In other studies, Prorocentrum minimum and P. lima caused decreased naupliar survival and impaired developmental speeds (Galvão, 2004; Ismar et al ., 2008), although they also were shown to be a good food source to fuel reproduction in some copepod species (Turner et al , 2001; Carotenuto et al , 2002; Ianora et al , 2004a). Gymnodinium sanguineum and Karenia brevis also adversely affected naupliar survival (Murray & Marcus, 2002; Turner et al , 2012), and Silva et al (2013) reported that Alexandrium tamiyavanichii and Gonyaulax sp. caused 88–100% mortality of Acartia lilljeborgii nauplii within a short time.…”
Section: Discussionmentioning
confidence: 99%
“…Zooplankton species may be affected by toxins showing sub-lethal symptoms such as changes in pulsation frequency and immobility [24], grazing and motility suppression [25], and even lethal responses [2627]. Moreover, HAB events may lead to shifts in community composition to more resistant species, generating complex cascading effects through the pelagic and benthic food webs [28]. Contaminated individuals may also transfer phycotoxins through the marine trophic web by the direct predation [2930], by the elimination of toxic cells in biodeposits and feces and through the release of toxins after their death making toxins available for detritivorous species [3133].…”
Section: Introductionmentioning
confidence: 99%